A cosmogenic 10Be anomaly during the late Miocene as independent time marker for marine archives - Dominik Koll; Johannes Lachner; Sabrina Beutner; Sebastian Fichter; Silke Merchel; Georg Rugel; Zuzana Slavkovská; Carlos Vivo-Vilches; Stella Winkler; Anton Wallner (Nature Communications)
Abstract Cosmogenic nuclide dating relies on the constancy of production and incorporation of radionuclides in geological archives. Anomalous deviations from constancy during the Holocene or Pleistocene are frequently used as global benchmarks to harmonize different data sets. A similar dating anchor on the million year timescale was so far not presented. In this work, we report on a prolonged cosmogenic 10Be anomaly during the late Miocene recorded in several Central and Northern Pacific deep-ocean ferromanganese crusts in the time period 9–11.5 Myr ago peaking at 10.1 Myr. Potential origins of this anomaly are discussed in the light of geological, climatic, solar and astrophysical events. This anomaly has the potential to be an independent time marker for marine archives.